(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2016)
Transition metal ions present in pulp, cause wasteful decomposition of hydrogen peroxide, a pulp brightener, and thus significantly affect the delignification selectivity of hydrogen peroxide bleaching. The metal ions also affect the brightness and optical properties of pulp. The free radicals generated during the decomposition degrade carbohydrates resulting in lower viscosity and yield. It is reported in the literature that magnesium sulfate successfully adsorbs transition metal ions and thus decrease their activity. This study dealt with the effect of Mg salts in hydrogen peroxide bleaching of jute caddies pulp. It was observed that prior bleaching treatments like chelation and acid washing of pulp were efficient in removing transition metal ions as indicated by lower consumption of hydrogen peroxide. However EDTA chelation seemed better compared to acid washing. The inclusion of Mg salts improved pulp brightness. The pulp viscosity was the highest with 0.3% Mg addition for both treated kraft and soda-AQ pulps. Considering both pulp viscosity and pulp brightness, it appeared that a 0.3% Mg dose on EDTA chelated pulp, was enough in hydrogen peroxide bleaching of pulps obtained from jute caddies. Bangladesh J. Sci. Ind. Res. 51(4), 291-296, 2016